The Dynamics of N(2)-O(3) and N(2)-SO(2) Probed by Microwave Spectroscopy. - Connelly, J; Meuwly, M; Auty, A; Howard, B (2000)
The microwave spectra of N(2)-O(3) and N(2)-SO(2) have been recorded in the 6-18 GHz range using a pulsed-nozzle, Fourier transform microwave spectrometer. C-type transitions have been observed for both complexes which are slightly shifted by internal tunneling motions of the O(3) or SO(2) moieties. In addition, unshifted a-type transitions have been observed for N(2)-O(3). The nuclear hyperfine pattern is typical of equivalent nitrogen nuclei. Two sets of rotational and hyperfine constants are required to fit the symmetric and antisymmetric nuclear spin states, indicating that the equivalence arises from tunneling rotation of the nitrogen molecule. Internal tunneling motions along three tunneling pathways have been identified, although no information on the N(2) tunneling frequency is available from the spectra. From the N(2)-O(3) data the tunneling frequencies cannot be decorrelated from the rotational parameters; however, the O(3) tunneling frequency upper limit is estimated to be 2.0 MHz and the frequency of the concerted tunneling motion of both moieties is estimated to be about 8.9 MHz. For N(2)-SO(2), the SO(2) tunneling frequency is 11.5 kHz and the concerted frequency 173.9 kHz. Both complexes are roughly T shaped with the N(2) axis approximately perpendicular to the O(3) or SO(2) plane. In the equilibrium structures of both complexes, the a-c inertial plane is a plane of symmetry. The centers of mass separations are estimated from the rotational parameters to be 3.582 Å for N(2)-O(3) and 3.875 Å for N(2)-SO(2). The angle between the symmetry axes of the O(3) or SO(2) and the line joining their centers of mass have been calculated as 130.84 degrees (or 49.16 degrees ) and 119.71 degrees (or 60.29 degrees ), respectively. From the quadrupole analysis, the average angle between the N(2) axis and the a-inertial axis is 32.12 degrees for N(2)-O(3) and 27.81 degrees for N(2)-SO(2). Model electrostatic and ab initio calculations confirm these structures. Differences between the experimental and calculated structural parameters highlight the role of tunneling dynamics in these complexes. Copyright 2000 Academic Press.